Rapid review of factors influencing dietary behaviors in Fiji - Boxer, Benjamin; Trübswasser, Ursula; Lesi, Viola; Naika, Asaeli; Dahal, Pradiumna; Sagan, Sonya; Joshi, Kshitij; Irache, Ana; Singh, Pragya; Nand, Devina; Kama, Ateca; Deo, Alvina; et al. (Frontiers in Nutrition, 2023)
Introduction: In Fiji, multiple burdens of malnutrition including undernutrition, overweight/obesity and micronutrient deficiencies coexist at the individual, household, and population level. Diets of children, adolescents and adults are generally unhealthy. The objective of this review was to understand how dietary behaviours of children, adolescents and women in Fiji are influenced by individual, social and food environment factors. Methods: This rapid review was conducted to synthesize existing evidence, identify research gaps in the evidence base and make recommendations for future research. The Cochrane Rapid Reviews Methods and the updated guideline for reporting systematic reviews were used. The search strategy for this rapid review was based on the Population Context Outcome (P(E)CO) framework, including search terms for population (children, adolescents, adults), context (Fiji) and outcome (dietary behaviours). Searches were conducted in PubMed, Scopus, PsycINFO and Google scholar. Results: The 22 studies included in this review identified different factors influencing dietary behaviours in Fiji. Individual preferences for processed and imported foods especially of younger generations and social dynamics, especially gender norms and social pressure to serve meat and overeat appeared to be prominent in driving dietary habits. The ongoing nutrition transition has led to an increasing availability and affordability of ultra-processed and fast foods, especially in urban areas. Concerns about food safety and contamination and climate change and its effect on local food production also appear to influence dietary choices. Discussion: This review identified different dynamics influencing dietary behaviours, but also research gaps especially with regard to the food environment, calling for an integrated approach to address these factors more systemically.